Neurosurgical Procedures Innovative Approaches - Scerrati, Alba; De Bonis, Pasquale (IntechOpen, 2020)
In the last few years, the development of new technologies in the medical field has allowed procedures and improved surgical techniques to be performed, which until recently would have been unthinkable.Modern neurosurgery is forever tied to technological progress: the development of robotics and robotic-assisted surgery; enhanced visualization, perfusion, and function monitoring in vascular surgery; new techniques of bone reconstruction; new cerebral imaging tools; and alternative treatments such as laser interstitial thermal therapy or immunotherapy for tumors. This book is designed to be a comprehensive introduction to these new developments and to their application in clinical practice. We have tried to provide a unique background and insights to coherently present these new technologies.